High Limit Penetration in Wind Power Research and Analysis of Static Voltage Stability Characteristics of the Regional Grid - Luo Qing; Chao Qin; Luo Jian-chun; Luo Jun; Xiao Liang-jian (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper established the high limit penetration power of a certain area including wind power grid model in 30.084% value, in the high limit penetration power transmission network by small disturbance voltage influence. Through the power flow calculation power flow distribution of the viewing area, with the reactive power compensation voltage were optimized. The impact on the system voltage load disturbance by PV-QV curve analysis. And its system reactive power margin and other issues. By the above calculation, the grid is analyzed in access high wind power penetration limit under the feasibility and reliability of operation, and its impact on the static voltage grid system analysis. Make wind power grid reliable access high penetration power frontier research.